Unlocking the potential of Rosa roxburghii Tratt polyphenol: a novel approach to treating acute lung injury from a perspective of the lung-gut axis - Tang, Li; Zhang, Shuo; Zhang, Min; Wang, Pengjiao; Liang, Guiyou; Gan, Zhitong; Gao, Xiuli (Frontiers in Microbiology, 2024)
Introduction Acute lung injury (ALI) is a serious respiratory disease characterized by progressive respiratory failure with high morbidity and mortality. It is becoming increasingly important to develop functional foods from polyphenol-rich medicinal and dietary plants in order to prevent or alleviate ALI by regulating intestinal microflora. Rosa roxburghii Tratt polyphenol (RRTP) has significant preventive and therapeutic effects on lipopolysaccharide-induced ALI mice, but its regulatory effects on gut homeostasis in ALI mice remains unclear. Methods This study aims to systematically evaluate the ameliorative effects of RRTP from the perspective of “lung-gut axis” on ALI mice by intestine histopathological assessment, oxidative stress indicators detection and short-chain fatty acids (SCFAs) production, and then explore the modulatory mechanisms of RRTP on intestinal homeostasis by metabolomics and gut microbiomics of cecal contents. Results The results showed that RRTP can synergistically exert anti-ALI efficacy by significantly ameliorating intestinal tissue damage, inhibiting oxidative stress, increasing SCFAs in cecal contents, regulating the composition and structure of intestinal flora, increasing Akkermansia muciniphila and modulating disordered intestinal endogenous metabolites. Discussion This study demonstrated that RRTP has significant advantages in adjuvant therapy of ALI, and systematically clarified its comprehensive improvement mechanism from a new perspective of “lung-gut axis”, which provides a breakthrough for the food and healthcare industries to develop products from botanical functional herbs and foods to prevent or alleviate ALI by regulating intestinal flora.